Оцінка конкурентоспроможності підприємств готельно-ресторанного бізнесу під час складання бізнес-плану - Якименко-Терещенко, Наталія Василівна (Причорноморський науково-дослідний інститут економіки та інновацій, 2018)
У статті розглянуто підходи до оцінки конкурентоспроможності підприємств готельноресторанного бізнесу. Акцентовано увагу на доцільності проведення та етапах оцінки впливу чинників на формування конкурентоспроможності підприємств готельно-ресторанного бізнесу.

The article considers approaches to evaluation of the competitiveness of enterprises engaged in hotel and restaurant business. Attention is drawn to the expediency of conduction and stages of evaluation the influence of factors on the formation of the competitiveness of enterprises engaged in hotel and restaurant business.
Evaluation of competitiveness of enterprises engaged in hotel-restaurant business when drafting a business plan
Keywords: бізнес-план; конкурентоспроможність; факторний аналіз; business plan; competitiveness; factor analysis